Prescribing Technology to Increase Uptake of Depression Treatment in Primary Care: A Pre-implementation Focus Group Study of SOVA (Supporting Our Valued Adolescents) - Radovic, Ana (J Clin Psychol Med Settings, 2020)
BACKGROUND: SOVA (Supporting Our Valued Adolescents) is a web-based technology intervention designed to increase depression and anxiety treatment uptake by adolescents in the context of an anonymous peer community with an accompanying website for parents. With a goal of informing the design of a hybrid effectiveness-implementation randomized controlled trial, we conducted a pre-implementation study in two primary care practices to guide implementation strategy development. METHODS: We conducted focus groups with primary care providers (PCPs) at 3 different timepoints with PCPs (14 total) from two community practices. A baseline survey was administered using Evidence-Based Practice Attitude Scale (EBPAS) and Physician Belief Scale (PBS). Subsequently, during each focus group, PCPs listened to a relevant presentation after which a facilitated discussion was audio recorded and transcribed. After timepoint 1, a codebook based on Consolidated Framework for Intervention Research (CFIR) and qualitative description were used to summarize findings and inform implementation strategies that were then adapted based on PCP feedback from timepoint 2. PCPs were provided with resources to implement SOVA over 5 months and then a third focus group was conducted to gather their feedback. RESULTS: Based on EBPAS and PBS, PCPs are willing to try new evidence-based practices and have positive feelings about taking care of psychosocial problems with some concerns about increased burden. During focus groups, PCPs expressed SOVA has a relative advantage and intuitive appeal, especially due to its potential to overcome stigma and reach adolescents and parents who may not want to talk about mental health concerns with their PCP. PCPs informed various implementation strategies (e.g. advertising to reach a wider audience than the target population; physical patient reminders). During timepoint 3, however, they shared they had a difficult time utilizing these despite their intention. PCPs requested use of champions and others to nudge them and priming of families with advertising, so that the PCP would not be required to initiate recommendation of the intervention, but only offer their strong endorsement when prompted. CONCLUSIONS: The process of conducting a pre-implementation study in primary care settings may assist with piloting potential implementation strategies and understanding barriers to their use. TRIAL REGISTRATION: NCT03318666